2019
DOI: 10.1001/jamanetworkopen.2019.3822
|View full text |Cite
|
Sign up to set email alerts
|

Viremia Trajectories of HIV in HIV-Positive Women in the United States, 1994-2017

Abstract: Key Points Question How do longitudinal viral trajectories vary among women with HIV? Findings In a cohort study of 1989 women, 3 trajectories were identified with low (28.6%), intermediate (39.4%), and high (32.0%) probability of viremia. Although younger age, African American or Hispanic race/ethnicity, depression symptoms, drug use, and unstable housing were associated with a high probability of viremia, between 2015 and 2017, 71.2% of women achieved sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
2
10
1
Order By: Relevance
“…In this study, indigenous ethnicity and age did not have an impact on VNS or PV. This differs from other studies where ethnic minorities [36,37] and younger populations [10,27,37,38] are more likely to experience worse outcomes in HIV care. Our findings may have been influenced by the low frequency of older PLHIV and those who self-identify as indigenous in our cohort, further studies are needed in these populations.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…In this study, indigenous ethnicity and age did not have an impact on VNS or PV. This differs from other studies where ethnic minorities [36,37] and younger populations [10,27,37,38] are more likely to experience worse outcomes in HIV care. Our findings may have been influenced by the low frequency of older PLHIV and those who self-identify as indigenous in our cohort, further studies are needed in these populations.…”
Section: Discussioncontrasting
confidence: 91%
“…Of 929 participants enrolled in the cohort, 664 had a recent viral load and had completed at least six months of ART. The median age was 39 years [interquartile range (IQR) [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], 356 (53.6%) were male, 493 (74.2%) were heterosexual and 99 (14.9%) self-identified with indigenous ethnicity. Almost half of the participants (49.2%) had less than or equal to primary education and only 60 (9.0%) had a bachelor's degree or higher.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the number of trajectories may be attributed to the difference in the sample size, the method of adherence measurement, and the time points at which adherence was measured. Of interest, the percentages of the consistently high, consistently moderate, and consistently low adherence trajectories in our analysis supported the findings of the study conducted by Kassaye et al 4 who used GBTM to delineate the long-term HIV viral suppression trajectories among women in WIHS. In their analysis, the women were grouped into 3 trajectories based on the probability of viremia above 200 copies/mL as low (28.6%), intermediate (39.4%), and high (32.0%).…”
Section: Discussionsupporting
confidence: 88%
“…2 HIV antiretroviral therapy (ART) maintains the health and well-being of an individual and reduces HIV transmission, which can be achieved through viral suppression. 3 Viral suppression among women is sub-optimal, for example, Kassaye et al 4 characterized the long-term HIV viral suppression among nearly 2000 women enrolled in the Women's Interagency HIV Study (WIHS); between 2015 and 2017, only 70% of the women demonstrated sustained viral suppression.…”
Section: Introductionmentioning
confidence: 99%
“…This value is higher than previously reported in findings from largely male cohorts of PWH (range, 3.0–5.3 log 10 copy-years/mL) [ 19 , 20 , 21 , 22 , 23 , 28 ]. In the HIV Outpatient Study, women had higher HIV-1 viral exposure than men [ 22 ], and previous WIHS data revealed younger age as a significant viremia risk factor [ 45 ]. Sex-differential drivers of viral exposure among treated PWH may include variability in antiretroviral drug exposure due to suboptimal adherence, food or drug interactions, drug pharmacokinetics (including drug penetration into cellular and/or tissue HIV reservoirs [ 46 ]), or socioeconomic strain disproportionately impacting women versus men [ 16 , 47 ].…”
Section: Discussionmentioning
confidence: 99%